2021
DOI: 10.4162/nrp.2021.15.5.568
|View full text |Cite
|
Sign up to set email alerts
|

Psidium guajava L. leaf extract inhibits adipocyte differentiation and improves insulin sensitivity in 3T3-L1 cells

Abstract: BACKGROUND/OBJECTIVES Psidium guajava L. (guava) leaves have been shown to exhibit hypoglycemic and antidiabetic effects in rodents. This study investigated the effects of guava leaf extract on adipogenesis, glucose uptake, and lipolysis of adipocytes to examine whether the antidiabetic properties are mediated through direct effects on adipocytes. MATERIALS/METHODS 3T3-L1 cells were treated with 25, 50, 100 µg/mL of methanol extract from guava leaf extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…3T3-L1 cell line is considered a classic cell line that has been frequently used in research such as adipocytes differentiation, glucose uptake, and lipid metabolism [ 42 ]. In recent years, more and more studies have reported the hypoglycemic activity of the plant extracts or active ingredients via glucose uptake experiments in 3T3-L1 adipocytes [ 43 , 44 ]. Our results showed that NBF possessed a significant dose-dependent effect on promoting glucose uptake in 3T3-L1 adipocytes, and the difference was statistically significant (*** p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…3T3-L1 cell line is considered a classic cell line that has been frequently used in research such as adipocytes differentiation, glucose uptake, and lipid metabolism [ 42 ]. In recent years, more and more studies have reported the hypoglycemic activity of the plant extracts or active ingredients via glucose uptake experiments in 3T3-L1 adipocytes [ 43 , 44 ]. Our results showed that NBF possessed a significant dose-dependent effect on promoting glucose uptake in 3T3-L1 adipocytes, and the difference was statistically significant (*** p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The glucose uptake model of 3T3-L1 cells is commonly used to study hypoglycemic ability. Recently, existing studies have reported that plant extracts or active components can promote glucose uptake in 3T3-L1 adipocytes to reduce blood glucose [ 23 , 32 ]. The results exhibited that NBF and NBF2 significantly promoted glucose uptake in 3T3-L1 adipocytes with dose-dependent effects, and the effect of NBF2 was more potent than NBF.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that polysaccharides from guava leaves could provide health benefits for diabetic patients. ( Choi et al, 2021 ) investigated the effects of guava leaf extract on adipogenesis, glucose uptake, and lipolysis of adipocytes and demonstrated that the extracts inhibits adipogenesis and improves adipocyte function by reducing basal lipolysis and increased insulin-stimulated glucose uptake in adipocytes, indicating the antidiabetic effects of guava leaves. These findings show that Psidium guajava L. can lower blood glucose and ameliorate body weight loss in diabetic mice.…”
Section: Medicinal Plants In Zimbabwe With Antidiabetic Propertiesmentioning
confidence: 99%